Systematic Identification of the Main Constituents from Agrimonia pilosa Ledeb. and Their Metabolites in Rats using HPLC-Q-TOF-MS/MS - Mengmeng, Song; Zhuicheng, Xu; Sixuan, Han; Xianjie, Sheng; Yan, Chen; Xinru, Li; Yan, Su; Qin, Li; Chenxiao, Shan; Tong, Xie; An, Kang (Planta Medica, 2022)
Agrimonia pilosa is a perennial herbaceous flowering plant, commonly known as agrimony or hairy agrimony. The dried aerial parts of this species have been widely used for the treatment of acute diarrhea, hemostasis, and other inflammation-related diseases. However, information on the in vivo metabolism of A. pilosa constituents is limited. In this study, the phytochemical profile of A. pilosa was investigated using HPLC-Q-TOF-MS/MS combined with a nontargeted diagnostic ion network analysis strategy. An information-dependent acquisition method with multiple filters was utilized to screen possible prototypes and metabolites in complex biological matrices. Furthermore, various data-processing techniques were applied to analyze possible prototypes and their metabolites in rat plasma, feces, and urine following oral administration of A. pilosa extract. A total of 62 compounds, which belonged to five main structural classes (21 phenols, 22 flavonoids, 6 coumarins, 3 triterpenes, and 10 organic acids), were tentatively identified in A. pilosa. In addition, using our proposed stepwise method, 32 prototypes and 69 metabolites were detected in rat plasma, feces, and urine. The main metabolic pathways after the oral administration of A. pilosa extract were revealed to include methylation, dihydroxylation, demethylation, hydrolysis, sulfation, and glucuronidation. This comprehensive in vivo and in vitro identification of the possible active components in A. pilosa could provide a basis for understanding its various pharmacological activities.
Keywords: Agrimonia pilosa; Rosaceae; HPLC-Q-TOF-MS/MS; chemical identification; metabolites